1971
DOI: 10.1161/01.cir.44.3.419
|View full text |Cite
|
Sign up to set email alerts
|

Direct Correlation of External Systolic Time Intervals with Internal Indices of Left Ventricular Function in Man

Abstract: Direct correlation of externally measured systolic time intervals with internally measured indices was obtained using catheter-tip micromanometers in six patients who had normal coronary arteriograms. Simultaneous recordings were made of central aorta and left ventricular pressure, maximum rate of rise in left ventricular pressure (dp/dt), external carotid pulse, external and internal sound, and electrocardiogram. Acute interventions were used to vary the indices by a variety of mechanisms including changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
10

Year Published

1974
1974
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(68 citation statements)
references
References 22 publications
5
53
0
10
Order By: Relevance
“…The same conclusions were reached by Martin et al [15]: the STI have been shown in man to correlate well with directly mea sured internal indices both under steady state conditions and during a series of interven tions including changes in contractivity, pre load. afterload and heart rate.…”
Section: Discussionsupporting
confidence: 79%
“…The same conclusions were reached by Martin et al [15]: the STI have been shown in man to correlate well with directly mea sured internal indices both under steady state conditions and during a series of interven tions including changes in contractivity, pre load. afterload and heart rate.…”
Section: Discussionsupporting
confidence: 79%
“…5,6,8 The internally measured systolic time intervals (PEP and LVET) correlate closely with the externally recorded PEP and LVET. 23,24 In addition, a highly significant correlation between the PEP/LVET and LV ejection fraction as measured by angiography has been demonstrated in a variety of cardiac diseases. 5 PEP prolongation, LVET shortening and an increase in PEP/LVET ratio is a characteristic pattern observed in patients with LV dysfunction, provided the patients are in sinus rhythm and do not have conduction defects or valvular heart diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As these parameters measured internally and externally were reported to correlate quite well with each other under various conditions (Martin et al 1971), the authors have tried to find out correlations mentioned above. As shown in Table 3, PEP and ICT were significantly prolonged from the control values by the inhalation of enflurane.…”
Section: Methodsmentioning
confidence: 99%